Use of reverse osmosis concentrate for mitigating greenhouse gas emissions from pig slurry - Im, Seongwon; Kang, Sungwon; Jang, Duksoo; Kim, Gyeongchul; Kim, Dong-Hoon (Frontiers in Microbiology, 2023)
Due to the high global warming potential (GWP) in a short time scale (GWP100 = 28 vs. GWP20 = 86), mitigating CH4 emissions could have an early impact in alleviating current global warming effects. A significant amount CH4 is emitting from the manure storage tank, which can diminish the environmental benefit resulted from the anaerobic digestion of manure that can generate renewable energy. Here, we added the reverse osmosis concentrate (ROC) rich in salt to the pig slurry (PS) storage tank to reduce CH4 emissions. Simultaneously, pure NaCl was tested at the same concentration to compare and verify the performance of ROC addition. During 40 d storage, 1.83 kg CH4/ton PS was emitted, which was reduced by 7-75% by ROC addition to 1-9 g Na+/L. This drop was found to be more intensive than that of adding pure sodium, which was caused by the presence of sulfate rich in ROC, resulting in the synergistic inhibition. Microbial community and activity test results showed sodium directly inhibited methanogenic activity rather than acidogenic. In the subsequent biogas production from the stored PS, more CH4 was attained by ROC addition, resulted from the preservation of organic matter during storage. Overall, 51.2 kg CO2 eq./ton PS was emitted during the storage while 8 kg CO2 eq./ton PS was reduced by biogas production in case of control, resulting in total 43.2 kg CO2 eq./ton PS. This amount of greenhouse gas emissions was reduced by ROC addition at 5 g Na+/L by 22 and 65 kg CO2 eq./ton PS, considering GWP100 and GWP20 of CH4, respectively, where most of reduction was achieved during the storage process. To our knowledge, this was the first report of using salty waste for reducing GHGs emissions in a proper place.